2019
DOI: 10.3390/su11195439
|View full text |Cite
|
Sign up to set email alerts
|

Study on Clustering of Free-Floating Bike-Sharing Parking Time Series in Beijing Subway Stations

Abstract: In recent years, the free-floating bike-sharing (FFBS) system has become a significant mode of travel to satisfy urban residents’ travel demands. However, with the rapid development of FFBS, many problems have arisen, among which the parking problem is the most prominent. To solve the FFBS parking problem around urban subways, firstly, the time series of FFBS parking pattern and subway station classification in Beijing were constructed based on parking intensity, showing a significant spatial distribution of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, shared bikes have obvious social attributes, which leads to the significant influence of media on residents' behaviors. Policies could encourage the recommendation of this environmentally-friendly travel mode to neighboring friends, relatives, and social contacts [7,45]. On the other hand, urban governments should dispel residents' anxieties through news media, social atmosphere, and word-of-mouth among groups [3] to improve residents' willingness to use shared bikes.…”
Section: Subjective Normsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, shared bikes have obvious social attributes, which leads to the significant influence of media on residents' behaviors. Policies could encourage the recommendation of this environmentally-friendly travel mode to neighboring friends, relatives, and social contacts [7,45]. On the other hand, urban governments should dispel residents' anxieties through news media, social atmosphere, and word-of-mouth among groups [3] to improve residents' willingness to use shared bikes.…”
Section: Subjective Normsmentioning
confidence: 99%
“…PBS (Figure 2b) is often run or subsidized by the government, involving massive docking station constructions, whilst FFBS is a newer form, which has been developing rapidly in China since 2016. It is found that FFBS ( Figure 2c) not only provides a new kind of sharing mode, but also gives rise to an unexpected change for sustainable transport [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On sidewalks, where the space for pedestrians is limited, the inconvenience is even greater. It also affects particularly vulnerable groups, such as people with reduced mobility [14]. A number of measures are already being taken, for example, through incentives to the users themselves [15], but others have to be implemented to regulate the zones for parking.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that social media activities in buildings with similar functions have comparable spatiotemporal patterns, a dynamic time warping (DTW) distance using a k-medoids method was applied to convert group buildings with similar social media activities into functional areas [17]. Some studies employed a time series analysis based on the DTW distances to explore the travel characteristics of the bike-sharing system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%